Lost in Learning: Hypertext Navigational Efficiency Measures Are Valid for Predicting Learning in Virtual Reality Educational Games - Ferguson, Chris; van Oostendorp, Herre (Frontiers in Psychology, 2020)
The lostness measure, an implicit and unobtrusive measure originally designed for assessing the usability of hypertext systems, could be useful in Virtual Reality (VR) games where players need to find information to complete a task. VR locomotion systems with node-based movement mimic actions for exploration and browsing found in hypertext systems. For that reason, hypertext usability measures, such as “lostness” can be used to identify how disoriented a player is when completing tasks in a serious educational game by examining steps made by the player. An evaluation of two different lostness measures, global and local lostness, based on two different types of tasks, is described in a VR educational game using 13 college students between 14 and 18 years old. Both lostness measures appeared to correlate with results on a post-game knowledge questionnaire but only one of these measures, local lostness, was significant. Therefore, we found that local lostness was able to predict how well participants would perform on a post-game knowledge test indicating how well they learned from the game. In-game experience aspects were also evaluated and, interestingly, it was also found that participants learned less when they felt more present in the game. We believe these two measures relate to cognitive overload, which is known to have an adverse effect on learning. Further research should investigate the lostness measure for use in an online adaptive game system and design the game system in such a way that cognitive load, and the risk of cognitive overload, is minimized when learning, resulting in higher retention of information.